2012
DOI: 10.1111/j.1748-1716.2012.02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alpha‐adrenergic effects on systemic vascular conductance during lower‐body negative pressure, static exercise and muscle metaboreflex activation

Abstract: Non-α-adrenergic vasoconstriction was present during LBNP. The systemic vasoconstriction during static exercise and isolated muscle metaboreflex activation, in the absence of leg vasoconstriction, was explained by an α-adrenergic mechanism. Therefore, non-α-adrenergic vasoconstriction is more emphasized during baroreflex, but not metaboreflex-mediated sympathetic activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
10
2
Order By: Relevance
“…grip exercise in healthy humans, the pressor response occurs via an increase in CO (16, 32, 34 -36, 57), an increase in TPR (6,17), or both of those (3,31,58,59,61,62). The variability of those findings leads one to speculate that there are considerable individual differences in the components of the pressor response to exercise, which is in stark contrast to the nearly invariant arterial pressure response.…”
contrasting
confidence: 49%
See 3 more Smart Citations
“…grip exercise in healthy humans, the pressor response occurs via an increase in CO (16, 32, 34 -36, 57), an increase in TPR (6,17), or both of those (3,31,58,59,61,62). The variability of those findings leads one to speculate that there are considerable individual differences in the components of the pressor response to exercise, which is in stark contrast to the nearly invariant arterial pressure response.…”
contrasting
confidence: 49%
“…While the increase in arterial pressure during isometric exercise is a well-established response, the responses of the components mediating the pressor response, cardiac output (CO) and total peripheral vascular resistance (TPR), remain controversial. In fact, previous studies have shown that, during isometric handgrip exercise in healthy humans, the pressor response occurs via an increase in CO (16,32,[34][35][36]57), an increase in TPR (6, 17), or both of those (3,31,58,59,61,62). The variability of those findings leads one to speculate that there are considerable individual differences in the components of the pressor response to exercise, which is in stark contrast to the nearly invariant arterial pressure response.…”
contrasting
confidence: 47%
See 2 more Smart Citations
“…Orthostatic stress can be induced nonpharmacologically by upright posture, or simulated using lower body negative pressure (LBNP). Many studies illustrate an increase in the groupaveraged forearm and leg vascular resistance during these tests (29,164,253,283) that are sensitive to norepinephrine (NE) release (253). In humans, head-up tilt elicits predictable increases in sympathetic outflow and total vascular resistance, the magnitude of which expresses interindividual variability (105).…”
Section: Baroreflexmentioning
confidence: 99%